O019 The Association between Later Circadian Timing and Higher Depressive Symptoms in Early Adolescence is Ameliorated by Longer Sleep Duration. (9th November 2022) - Chachos, E; Lu, S; Hand, A; Carskadon, M; Klerman, E; Lockley, S; Wiley, J; Phillips, A; Rajaratnam, S; Bei, B; Stone, J
Abstract: Background: Circadian phase and sleep-wake timing delays are hallmark adolescent development features. These delays contribute to shorter sleep duration in combination with early school schedules. Both delayed circadian phase and insufficient sleep are associated with increased prevalence/severity of mood problems. This study examined associations between circadian phase, sleep duration, and mood in early adolescence. Methods: 157 Year 7 Australian students (M±SD=12.81±0.40 years, 56.7% female) wore actiwatches and completed sleep diaries for two weeks in school term. Circadian phase was measured via salivary dim light melatonin onset (DLMO) on the final Friday of sleep monitoring. PROMIS Paediatric Depression and Anxiety measured depression/anxiety symptom severity. Sleep duration/efficiency were calculated using actigraphy and self-reports. Multiple linear regression quantified the relationships between sleep duration and efficiency and circadian phase and mood (depression/anxiety) associations, adjusting for sex. Results: DLMO occurred at the expected time for early adolescents [continuous decimal time; M±SD=20.52±1.20; range:17.52-24.03]. Sleep duration (p=.03), but not sleep efficiency (p=.89), moderated associations between DLMO and depression (but not anxiety; p-values>.08). Simple slope analyses showed that in individuals with shorter average sleep duration, a one-hour circadian phase delay was associated with 1.84 t-score increase in depressive symptom severity (p=.03). These associations were non-significant in individuals with longer average sleep duration (p=.44). Conclusion: Although delayed circadian phase is a developmental norm, its association with increased depressive symptom severity was ameliorated in young adolescents who obtained longer sleep duration. Addressing sleep duration, a modifiable protective factor (e.g., by delaying school start times), may yield mood-related benefits for adolescents.